Supported Science and Reproductive Technology to Achieve Cows Pregnancy Program Succesfully - Ismeth Inounu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Special efforts (UPSUS) to make cows pregnant (SIWAB) is a program to accelerate cattle population to meet the demand of animal origin food through artificial insemination or intensification of natural mating. Experience shows that a similar program that has been conducted previously was less successful. This paper aims to give some information on science, technology, and management of cattle reproduction that require attention to achieve SIWAB program successfully. Several things should be concerned for this program are: (1) Selection of fertile females and bulls; (2) Natural mating or artificial insemination (availability of semen, liquid nitrogen, supporting equipment, and inseminator); (3) Early detection of pregnancy; (4) Feed and feeding management; (5) Control of reproduction disease and other diseases; and (6) The supervision and handling of pregnant cows during and after birth. Another important thing that should be taken into account is the preparation of mating calendar so that the birth will occur during the period of abundant feed resources, and management of optimal forage and supplements to ensure good body condition of cows at the time of calving. With an understanding of science, technology, and applying reproductive management, it is expected that the targeted pregnancy cows by UPSUS program can be obtained.